Ecology and management of grapevine trunk diseases in New Zealand a review - Mundy, D.C.; Manning, M.A. (New Zealand Plant Protection, 2010)
Grapevine trunk diseases threaten the longevity of vineyard production in New Zealand This paper provides a summary of the knowledge of the most common fungal grapevine trunk diseases as well as identifying gaps that require further research Current knowledge of symptoms causal organisms etiology and disease control of botryosphaeria dieback esca eutypa dieback and Petri disease are discussed Additional information about how these diseases may be influenced by different vineyard practices common in New Zealand viticulture is provided